2017
DOI: 10.1111/aos.13485
|View full text |Cite
|
Sign up to set email alerts
|

Retinal venous pressure is higher than the airway pressure and the intraocular pressure during the Valsalva manoeuvre

Abstract: During the VM, the RVP was increased compared with the ∆AirP. The increase in RVP (∆RVP) was significantly greater than the ∆IOP. During the VM, the calculated retinal perfusion pressure may be more strongly reduced by the ∆RVP than by the ∆IOP. These properties may influence retinal and optic nerve head pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Fear of a negative effect of vaginal delivery on the worsening of eye functions among women with eye disorders stems mostly from measurements showing that intraocular pressure increases, on average, by 0.8 mm Hg during the Valsalva maneuver, and the pressure in ocular veins rises even more significantly . However, vaginal delivery is safe from an ophthalmologic point of view, and there is currently no existing ophthalmologic indication for cesarean .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of a negative effect of vaginal delivery on the worsening of eye functions among women with eye disorders stems mostly from measurements showing that intraocular pressure increases, on average, by 0.8 mm Hg during the Valsalva maneuver, and the pressure in ocular veins rises even more significantly . However, vaginal delivery is safe from an ophthalmologic point of view, and there is currently no existing ophthalmologic indication for cesarean .…”
Section: Discussionmentioning
confidence: 99%
“…6 In the pres- veins rises even more significantly. 8 However, vaginal delivery is safe from an ophthalmologic point of view, and there is currently no existing ophthalmologic indication for cesarean. 9 In spite of this, 74.0% of obstetricians in Europe indicate cesarean for women with a history of rhegmatogenous retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…; Wong & White ; Stodtmeister et al. ). This leads to a lower than expected OPP, since current formulas oversimplify the complex physiology by assuming that IOP is a correct measure for ocular venous pressure in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Central retinal vein (CRV) pressure has been shown to be higher than the IOP in a large part of glaucoma patients (Stodtmeister 2015). This was objectively measured, but could also be hinted by the absence of CRV pulsation on fundoscopy (Morgan et al 2004(Morgan et al , 2005Harder & Jonas 2007;Abegao Pinto et al 2013;Wong & White 2013;Stodtmeister et al 2018). This leads to a lower than expected OPP, since current formulas oversimplify the complex physiology by assuming that IOP is a correct measure for ocular venous pressure in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the VM may lead to an increase in intraocular pressure (IOP), although the mechanisms remains unclear [3,[9][10][11]. Schuman et al suggested that an elevation in IOP is caused by increased uveal volume via the VM, although the observed IOP was much less than the calculated effect on IOP based on the measured change in uveal volume [12].…”
Section: Introductionmentioning
confidence: 99%